2015
DOI: 10.1038/srep09097
|View full text |Cite|
|
Sign up to set email alerts
|

Apoptotic effect of novel Schiff Based CdCl2(C14H21N3O2) complex is mediated via activation of the mitochondrial pathway in colon cancer cells

Abstract: The development of metal-based agents has had a tremendous role in the present progress in cancer chemotherapy. One well-known example of metal-based agents is Schiff based metal complexes, which hold great promise for cancer therapy. Based on the potential of Schiff based complexes for the induction of apoptosis, this study aimed to examine the cytotoxic and apoptotic activity of a CdCl2(C14H21N3O2) complex on HT-29 cells. The complex exerted a potent suppressive effect on HT-29 cells with an IC50 value of 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 50 publications
3
25
0
Order By: Relevance
“…Most approaches applied in cancer therapy, such as chemotherapy and radiation therapy, are likely to be affected by the apoptotic activities of tumor cells, leading to apparent therapeutic implications. Many morphological and biochemical changes are associated with cell apoptosis, which include nuclear fragmentation, mitochondrial potential change, caspase activation, and so on 30 38 . In our study, the release of cytochrome c from mitochondria into the cytosol and the activation of caspase cascades were observed in A- and B-treated MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most approaches applied in cancer therapy, such as chemotherapy and radiation therapy, are likely to be affected by the apoptotic activities of tumor cells, leading to apparent therapeutic implications. Many morphological and biochemical changes are associated with cell apoptosis, which include nuclear fragmentation, mitochondrial potential change, caspase activation, and so on 30 38 . In our study, the release of cytochrome c from mitochondria into the cytosol and the activation of caspase cascades were observed in A- and B-treated MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The MTT results obtained in this experiment revealed that the new quinazolinone Schiff bases selectively inhibited MCF-7 cancer cell viability without affecting breast cancer cells MDA-MB-231 and the normal cells (MCF 10A and WRL-68). The apoptotic effect of these compounds were further established using microscopic analysis by AO/PI staining, which showed distinctive morphological changes associated with typical apoptosis features, such as chromatin condensation and membrane blebbing 30 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Their active metal groups and ligands are mainly attributed to their therapeutic activities 30 31 . Based on the promising anticancer role of CdCl2(C14H21N3O2) complex on HT-29 cells which was supported through different mechanistic pathways such as release of lactate dehydrogenase (LDH), reactive oxygen species (ROS) production, effect on mitochondria membrane potential (MMP), caspase activation which was conducted by our group 32 , we planned to proceed on in-vivo analysis. It is critical to report the safety and the proper and efficient route for the administration of these novel anticancer agents for the development of drugs based on the global harmonised system of classification and labelling of chemicals 33 34 .…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, considerable attention has focused on the development of Schiff base metal complexes due to their electroluminescent properties [50], biological activities (such as antiviral, antibacterial, antiapoptotic, antifungal, anti-inflammatory activities and as urease inhibitors) [51][52][53][54]. Schiff base complexes show nonlinear optical (NLO) properties [55][56][57], DNAbinding properties [58][59][60][61] and fluorescence properties [62][63][64][65].…”
Section: Figmentioning
confidence: 99%